The synthesis of an electron deficient diene and progress towards the first total synthesis of jatrorrhizine - Swinamer, Alan, 1968- (1997)
Thesis (M. Sc.)--Memorial University of Newfoundland, 1998. Chemistry Bibliography: leaves 135-151 In process